Seismic Performance of a New Slurry-Anchored Connected Precast Concrete Shear Walls with Vertical Reinforcement - Yuqi Liu; Quandong Xiao; Xingwen Yin (Geofluids)
The effectiveness of joint connection mode of PC shear wall structure directly determines the integrity and seismic performance of the structure. In this paper, a new type of grout-anchor connection of PC shear wall with closed stirrup constraint is proposed. For the investigation of the seismic performance of these shear walls, one cast-in-place shear wall specimen and two new slurry-anchored lap PC shear wall specimens were subjected to quasistatic test. The experimental results were verified and parametrically analyzed using the ABAQUS software. The test results showed that the slurry-anchored connection with buckled closed stirrups restraint could effectively transfer the stress. The PC shear walls and cast-in-place shear walls exhibited similar seismic performance and both exhibited bending shear damage when damaged. In general, the PC shear walls had a stronger bearing capacity and better displacement ductility performance than cast-in-place shear walls. Their energy dissipation capacity was similar to that of cast-in-place shear walls, but their initial stiffness was lower than that of cast-in-place shear walls. The numerical simulation results showed that, by increasing the axial compression ratio, the vertical connection reinforcement diameter, and the concrete strength, the stiffness and the load-carrying capacity of the horizontally jointed assembled shear wall structure could be improved within a certain range. With an increase in the height-to-width ratio, the peak load of the PC shear wall model decreased, while the ductility and the energy dissipation capacity were enhanced.